Determinan Kualitas Laporan Keuangan Pemerintah Desa di Kabupaten Kediri Jawa Timur dengan Menggunakan Peran Pendamping Desa sebagai Pemoderasi - Subehan, Achmad; Harnovinsah, Harnovinsah; Ahmar, Nurmala (Value : Jurnal Manajemen dan Akuntansi, 2024)
The government has developed a village financial system application (Siskeudes) as a tool to assist villages in achieving financial accountability. The operation of this application requires training and mentoring. The government also provides village mentoring, which is currently offered by the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration. This research aims to analyze the factors that influence the quality of village government financial reports in Kediri Regency with the professional village facilitator as a moderating variable. These factors are Understanding of Government Accounting Standards, Implementation of Village Financial System Application (Siskeudes), and The professional Village Facilitator. This research is a quantitative research using primary data through distributing questionnaires. The population and sample in this research were the village secretaries or village finance officers in the Kediri Regency. The survey was conducted on 100 respondents in 100 villages out of 343 villages in Kediri Regency. Data were analyzed using Structural Equation Modeling using WarpPLS 7.0 software. The results showed that understanding of government accounting standards, village financial system application (Siskeudes), and the professional village facilitators significantly affected the quality of village government financial reports. The professional village facilitator can moderate the influence between understanding of government accounting standards and village financial systems application (Siskeudes) on the quality of village government financial reports.